Large-scale deployment of electric vehicles in Germany by 2030: An analysis of grid-to-vehicle and vehicle-to-grid concepts - Loisel, Rodica; Pasaoglu, Guzay; Thiel, Christian (Elsevier BV, 2014)
Abstract This study analyses battery electric vehicles (BEVs) in the future German power system and makes projections of the BEVs hourly load profile by car size (‘mini’, ‘small’, ‘compact’ and ‘large’). By means of a power plant dispatching optimisation model, the study assesses the optimal BEV charging/discharging strategies in grid-to-vehicle (G2V) and vehicle-to-grid (V2G) schemes. The results show that the 2% rise in power demand required to power these BEVs does not hamper system stability provided an optimal G2V scheme is applied. Moreover, such BEV deployment can contribute to further integrating wind and solar power generation. Applying a V2G scheme would increase the capacity factors of base and mid-load power plants, leading to a higher integration of intermittent renewables and resulting in a decrease in system costs. However, the evaluation of the profitability of BEVs shows that applying a V2G scheme is not a viable economic option due to the high cost of investing in batteries. Some BEV owners would make modest profits (€6 a year), but a higher number would sustain losses, for reasons of scale. For BEVs to become part of the power system, further incentives are necessary to make the business model attractive to car owners.
Keywords: Power plants; Dispatching model; Electric cars; [SPI.NRJ]Engineering Sciences [physics]/Electric power; Electric cars, Vehicle-to-grid, Power plants, Dispatching model; Vehicle-to-grid; [SHS]Humanities and Social Sciences; [SPI.GCIV.IT]Engineering Sciences [physics]/Civil Engineering/Infrastructures de transport; [SHS] Humanities and Social Sciences